An investigation on the wind profiles and gravity wave dynamics in MLT region based on the meteor radars from the Meridian Project - Tai Liu; Zhe Wang; MengXi Shi; Willie Soon; ShiCan Qiu (Earth and Planetary Physics)
The meteor radar can detect the zenith angle, azimuth, radial velocity, and altitude of meteor trails so that one can invert the wind profiles in the mesosphere and low thermosphere (MLT) region, based on the Interferometric and Doppler techniques. In this paper, the horizontal wind field, gravity wave (GW) disturbance variance, and GW fluxes are analyzed through the meteor radar observation from 2012−2022, at Mohe (53.5°N, 122.4°E) and Zuoling (30.5°N, 114.6°E) stations of the (Chinese) Meridian Project. The Lomb−Scargle periodogram method has been utilized to analyze the periodic variations for time series with observational data gaps. The results show that the zonal winds at both stations are eastward dominated, while the meridional winds are southward dominated. The variance of GW disturbances in the zonal and meridional directions increases gradually with height, and there is a strong pattern of annual variation. The zonal momentum flux of GW changes little with height, showing weak annual variation. The meridional GW flux varies gradually from northward to southward with height, and the annual periodicity is stronger. For both stations, the maximum values of zonal and meridional wind occur close to the peak heights of GW flux, with opposite directions. This observational evidence is consistent with the filtering theory. The horizontal wind velocity, GW flux, and disturbance variance of the GW at Mohe are overall smaller than those at Zuoling, indicating weaker activities in the MLT at Mohe. The power spectral density (PSD) calculated by the Lomb−Scargle periodogram shows that there are 12-month period and 6-month period in horizontal wind field, GW disturbance variance and GW flux at both stations, and especially there is also a 4-month cycle in the disturbance variance. The PSD of the 12-month and 6-month cycles exhibits maximum values below 88 km and above 94 km.